Interaction between autophagy and the NLRP3 inflammasome in Alzheimer’s and Parkinson’s disease - Lu, Ranran; Zhang, Lijie; Yang, Xinling (Frontiers in Aging Neuroscience, 2022)
Autophagy degrades phagocytosed damaged organelles, misfolded proteins, and various pathogens through lysosomes as an essential way to maintain cellular homeostasis. Autophagy is a tightly regulated cellular self-degradation process that plays a crucial role in maintaining normal cellular function and homeostasis in the body. The NLRP3 inflammasome in neuroinflammation is a vital recognition receptor in innate cellular immunity, sensing external invading pathogens and endogenous stimuli and further triggering inflammatory responses. The NLRP3 inflammasome forms an inflammatory complex by recognizing DAMPS or PAMPS, and its activation triggers caspase-1-mediated cleavage of pro-IL-1β and pro-IL-18 to promote the inflammatory response. In recent years, it has been reported that there is a complex interaction between autophagy and neuroinflammation. Strengthening autophagy can regulate the expression of NLRP3 inflammasome to reduce neuroinflammation in neurodegenerative disease and protect neurons. However, the related mechanism is not entirely clear. The formation of protein aggregates is one of the standard features of Neurodegenerative diseases. A large number of toxic protein aggregates can induce inflammation. In theory, activation of the autophagy pathway can remove the potential toxicity of protein aggregates and delay the progression of the disease. This article aims to review recent research on the interaction of autophagy, NLRP3 inflammasome, and protein aggregates in Alzheimer’s disease (AD) and Parkinson’s disease (PD), analyze the mechanism and provide theoretical references for further research in the future.